2023
DOI: 10.3390/gels9060448
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Solid Dosage Forms Containing Pranoprofen-Loaded NLC as Topical Therapy for Local Inflammation: In Vitro, Ex Vivo and In Vivo Evaluation

Abstract: Pranoprofen (PRA)-loaded nanostructured lipid carriers (NLC) have been dispersed into blank gels composed of 1% of Carbomer 940 (PRA-NLC-Car) and 3% of Sepigel® 305 (PRA-NLC-Sep) as a novel strategy to refine the biopharmaceutical profile of PRA, for dermal administration in the treatment of skin inflammation that may be caused by possible skin abrasion. This stratagem intends to improve the joining of PRA with the skin, improving its retention and anti-inflammatory effect. Gels were evaluated for various para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…Furthermore, under a constant rate cycle of 50 s −1 , the mean viscosity values at 25 • C were 12.18 ± 0.26 Pa•s for H-Blank and 12.46 ± 0.42 Pa•s for HMX − RM, respectively. Similar increases at low shear rate values (50 s −1 ) have been previously observed in guar gum hydrogels loaded with different drugs, maintaining a decreased viscosity when the shear rate increases, which is a critical property for easy topical administration [37]. In addition, different studies indicated that the viscosity of the hydrogels played an important role in the percentage of drug release [6].…”
Section: Characterization Of Hpg Hydrogels 251 Viscosity Studiessupporting
confidence: 77%
See 2 more Smart Citations
“…Furthermore, under a constant rate cycle of 50 s −1 , the mean viscosity values at 25 • C were 12.18 ± 0.26 Pa•s for H-Blank and 12.46 ± 0.42 Pa•s for HMX − RM, respectively. Similar increases at low shear rate values (50 s −1 ) have been previously observed in guar gum hydrogels loaded with different drugs, maintaining a decreased viscosity when the shear rate increases, which is a critical property for easy topical administration [37]. In addition, different studies indicated that the viscosity of the hydrogels played an important role in the percentage of drug release [6].…”
Section: Characterization Of Hpg Hydrogels 251 Viscosity Studiessupporting
confidence: 77%
“…The viscosity results for these hydrogels with a constant shear rate of 50 s −1 were 9.22 ± 0.26, 12.18 ± 0.26, and 17.45 ± 0.28 Pa·s for blank HPG hydrogels with percentages of 1.0, 1.75 and 2.5%, respectively. These results showed that a gelling agent concentration of 1.75% ( w / v ) HPG produced a gel with adequate viscosity values, which would be suitable for topical administration [ 5 , 37 ]. This concentration was selected for further analysis: viscosity, FTIR, SEM, dissolution, and kinetic studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports in the literature have demonstrated that insoluble and biodegradable polymers and their composites and hybrids can be exploited as carriers to manipulate the gradual release of the loaded drug molecules [ 75 , 76 , 77 , 78 ]. Meanwhile, lipid materials are also frequently explored for the extended release of drugs in the formation of microparticles, micelles, composites, solid nanoparticles, emulsions, and liposome [ 79 , 80 , 81 , 82 , 83 ]. Thus, firstly, in this study, both insoluble polymer EC gels and the lipid SA were selected as the TC carrier, which are materials selected from experiences with the traditional pharmaceutics.…”
Section: Resultsmentioning
confidence: 99%
“…Among the ways of application of colloidal systems based on solid lipids extensively documented in the literature are cosmetic [5,8,9], food [4,6,10], and, above all, in the pharmaceutical industry (i.e., drug delivery) [7,11,12]. In recent years, lipid formulations have enabled the effective encapsulation of active substances successfully delivered intravenously [13][14][15], orally [16][17][18], transdermally [19][20][21], and also directly into the eye [22][23][24] or nose [25][26][27].…”
Section: Introductionmentioning
confidence: 99%